Something in the Air: Pollution and the Demand for Health Insurance - Chang, Tom Y; Huang, Wei; Wang, Yongxiang (Review of Economic Studies, 2018)
We find that daily air pollution levels have a significant effect on the decision to purchase or cancel health insurance in a manner inconsistent with rational choice theory. A one standard deviation increase in daily air pollution leads to a 7.2% increase in the number of insurance contracts sold that day. Conditional on purchase, a one standard deviation decrease in air pollution during the cooling-off (i.e. cost-free cancellation) period relative to the order-date level increases the return probability by 4.0%. We explore a range of potential mechanism and find the most support for projection bias and salience.